A COMPARATIVE STUDY BETWEEN ENGLISH AND KOREAN INTERROGATIVE SENTENCES - Kurniawan, Eddy; Silvia, Resi (LPPM Universitasdiwangsa Jambi, 2021)
This study discusses English And Korean Interrogative Sentences. It is aimed at describing the forms and types of English and Korean Interrogative Sentences and finding out the similarities and the differences between English and Korean Interrogative Sentences. This research belongs to descriptive and comparative type. The research object in this study is English and Korean Interrogative Sentences. And the data form in this study is the sentences. The researcher took the sources of data from English and Korean grammar books, English and Korean magazines, English and Korean newspapers, English students books for high school published by Erlangga, and Korean course students books. The techniques for collecting data used noting technique, separating technique, and transferring technique. The data analyzing techniques used three technique; they are description, interpretation and analysis. The result of this research showed that the types of English interrogative sentences are ‘Ye/No Question, WH-Question, Subject Question, and Tag Question’. The types of Korean interrogative sentences are ‘Yes/No interrogative, Alternative interrogative, WH-interrogative, and Tag Question’. The forms of English interrogative sentences are ‘Yes/No Questions with Auxiliary Be, Auxiliary Do/Does/Did, Auxiliary Have/Has/Had, Modal Auxiliary, WH-Questions with Auxiliary Be, Auxiliary Do/Does/Did, Auxiliary Have/Has/Had, Modal Auxiliary, Subject Questions with Auxiliary Be, Auxiliary Do/Does/Did, Auxiliary Have/Has/Had, Modal Auxiliary, Tag Questions with Auxiliary Be, Auxiliary Do/Does/Did, Auxiliary Have/Has/Had, Modal Auxiliary.’ The forms of Korean interrogative sentences are ‘Yes/No Interrogatives with Final Ending, Interrogative with Final Ending, Interrogative with Final Ending